A Critical Examination of Maize Yield Response to Tillage, Traffic and Soil Temperature on a Ferruginous Soil (Haplustalf) - Yusuf, D.D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
Compaction of agricultural soils due to multiple passes of heavy power units has been the subject of much concern, in recent years. This paper, through a 3-year on-farm experiment, studied and discussed the resulting effects of tillage, traffic compaction and soil temperature on maize yield. Results showed that soil resistance to cone penetration and crop yield changed rapidly during the period of study and could be related to soil moisture content and tillage. As maize extracts soil moisture, differential soil strengths and crop yields were obtained between shallow and deep tilled plots. Soil temperatures were lower in shallow (15.0 xm) tilled plots than in deep (30.00cm) tilled plots and high soil temperature enhanced maize grain yield. The most rapid seedling emergence and highest crop yield were obtained in soil temperatures that averaged 300C at seedling level and within the top soil of 0-15cm zone. Increase in soil resistance to cone penetration reduced maize grain yield. Tillage treatment significantly affected (soil temperature, plant height and maize grain yield.